Two different genogroups of Ehrlichia canis from dogs in Thailand using immunodominant protein genes - Nambooppha, Boondarika; Rittipornlertrak, Amarin; Tattiyapong, Muncharee; Tangtrongsup, Sahatchai; Tiwananthagorn, Saruda; Chung, Yang-Tsung; Sthitmatee, Nattawooti (Infection, genetics and evolution, 2018)
Ehrlichia canis is the causative agent of canine monocytic ehrlichiosis (CME). While there is a high prevalence of CME in Thailand, genetic diversity of E. canis is still poorly defined. This study examined the molecular characteristics of E. canis using PCR and phylogenetic analysis of the dsb, gp19 and gp36 genes. DNA was extracted from 220 whole blood samples of naturally infected dogs, and all had clinical signs compatible with tick-borne diseases. Of these, 16.4% (36/220) provided positive E. canis DNA via the dsb and gp19 genes. However, only 13 out of the 36 samples (36.1%) were positive for the gp36 gene. Sequences of the dsb gene had very high identity (99–100%) with previously deposited E. canis sequences. Sequences of the gp19 gene were similar to those from US and Taiwanese genogroups (98.8–99.5% identity). Elucidation of genetic characteristics of E. canis based on the gp36 gene displayed 91.4–99.1% shared identity. There were 426–429 bp of a 5′ end pre-repeat tandem region, a 27 bp repetition with variable numbers of a tandem repeat (TR) region of 9 amino acid sequences (TEDSVSAPA), and a variable 3′ end region with sequence length depending on the isolate (72–93 bp). Phylogenetic trees of E. canis, particularly using the gp36 amino acid sequences, showed that the Thai strains fell into two phylogenetic clades contained within other worldwide E. canis strains. Alignment and phylogenetic analysis suggested that E. canis strains from Thailand could be divided into two genogroups, the US and Taiwanese genogroups. This study provides the first characterization of the dsb and gp19 genes of E. canis in Thailand, the results support the conclusion that the gp36 is a potential target for genotyping and elucidation of phylogenetic relationships among E. canis strains. •This is the first report of E. canis dsb and gp19 characterization in Thailand.•Two genogroups of E. canis strains in Thailand using immunoreactive protein genes, gp19 and gp36 are proposed.•The gp19 gene, highly conserved, is one of potential target gene for diagnosis and vaccine development worldwide.•The gp36 is a promising target for evaluation of the genetic diversity of E. canis strains.